Content Analysis Of English Textbook “Think Globally Act Locally” For Ninth-Grade Students Based On Curriculum 2013 - Ria Rizky Rahmadhani; Sri Handayani (Pusat riset dan Inovasi Nasional, 2023)
The aim of this research is to analyse the suitable contents of the material in an English textbook entitled “Think Globally Act Locally” for ninth grade students of Junior High School focused on the accuracy of the materials based on BSNP (Badan Standar Nasional Pendidikan) by using rubric assessment. The research design of the research is content analysis with descriptive qualitative. The result of the research showed that not all chapters of the textbook entitled “Think Globally Act Locally” were appropriated by the criteria according to BSNP. The researcher found that only 68.75% of the materials that fulfilled the rubric criteria of BSNP focused on the accuracy of the materials. From the result, the researcher concludes that based on the rubric assessment, the accuracy of the materials in the English textbook entitled “Think Globally Act Locally” for ninth grade students of Junior High School appropriate with the content standard from BSNP and good to be used in the teaching learning process.